Determinants of antenatal care attendance among women in Akabiluru District: A cross-sectional study - Vittria Meilinda; Qualita Fadhila Darsi (International Journal on Health and Medical Sciences, 2026)
Antenatal care (ANC) is essential for the early detection of pregnancy complications and the preparation for safe childbirth. Despite national targets of 90% coverage for the fourth ANC visit (K4) and 80% for the sixth ANC visit (K6), ANC utilization in Akabiluru District remains below these standards. In 2024, K4 and K6 coverage reached only 65.2% and 67.6%, respectively, at Piladang Primary Health Center, while Batu Hampar Primary Health Center reported lower rates of 42.0% and 36.0%. This study aimed to identify factors associated with ANC visits among women in Akabiluru District. A descriptive quantitative study with a cross-sectional design was conducted among 48 postpartum mothers within two months after delivery, selected through total sampling. Data were collected using structured questionnaires and analyzed using frequency distribution and Chi-square tests. The findings revealed that most respondents were aged 20–34 years (79.2%), multiparous (66.7%), had completed senior high school education (58.3%), and had family incomes below the regional minimum wage (66.7%). More than half of the respondents had low knowledge (58.3%) and did not complete the recommended ANC visits (58.3%). Bivariate analysis showed that attitude (p=0.000), motivation (p=0.001), husband’s support (p=0.008), and access to information media (p=0.000) were significantly associated with ANC visits. Knowledge, healthcare provider support, and socio-cultural factors were not significantly associated. Strengthening health promotion, antenatal education, and family planning programs may improve ANC utilization among pregnant women.